PEDOT:PSS self-assembled films to methanol crossover reduction in Nafion (R) membranes - Almeida, Tiago P.; Miyazaki, Celina Massumi [UNESP]; Paganin, Valdecir A.; Ferreira, Marystela; Saeki, Margarida Juri [UNESP]; Perez, Joelma; Riul, Antonio (Elsevier B.V., 2014)
Alternative energy sources are on a global demand, with fuel cells as promising devices from mobile to stationary applications. Nafion (R) is at the heart of many of these appliances, being mostly used due to its high proton conduction and good chemical stability at ambient temperature in proton exchange membranes (PEM). Therefore, methanol permeation throughout Nafion (R) films reduces drastically the performance of direct methanol fuel cells (DMFC). We present here the deposition of layer-by-layer (LbL) nanostructured thin films of poly(allylamine hydrochloride) (PAH) and poly(3,4-ethylenedioxythiophene)poly(styrenesulfonate) (PEDOT:PSS) onto commercial Nafion (R) 212 membranes. It was observed a good adherence of the LbL films onto Nafion (R) 212, with UV-vis results displaying a linear characteristic growth, indicative that the same amount of material was deposited at each deposition step during the layer-by-layer assembly. In addition, the LbL films also act as a good barrier to avoid methanol crossover, with an observed reduction in the methanol permeation from 5.5 x 10(-6) cm(2) s(-1) to 3.2 x 10(-6) cm(2) s(-1), respectively to pristine Nafion (R) 212 and a 5-bilayer PAH/PEDOT:PSS LbL film deposited on Nafion (R) 212. The measured power density in a DMFC set-up was not significantly changed (similar to 12 mW cm(-2)) due to the LbL films, since the PAH/PEDOT:PSS nanostructure is impeding water and ion transport, consequently affecting the proton conduction throughout the membrane. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Direct methanol fuel cell; Crossover; Layer-by-layer; PEDOT:PSS